2001
DOI: 10.1176/appi.ajp.158.7.1114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Schizophrenia on Frontotemporal Activity During Word Encoding and Recognition: A PET Cerebral Blood Flow Study

Abstract: Left frontotemporal activation during episodic encoding and retrieval, which is associated with better recognition in healthy people, is disrupted in schizophrenia despite relatively intact recognition performance and right prefrontal function. This may reflect impaired strategic use of semantic information to organize encoding and facilitate retrieval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
78
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 95 publications
13
78
1
Order By: Relevance
“…Given the role of the anterior cingulate in monitoring of error commission [Ghering et al, 1993], Carter et al [2001] speculated that increased activity in the anterior cingulate and decreased activity in the DLPFC might occur if patients have impaired attentional control leading to greater response conflict and demands for error monitoring. The increased frontal pole activity found in the current study has also been seen in previous studies of verbal episodic memory [Heckers et al, 1998;Ragland et al, 2001] and attributed to increased retrieval effort in the patient sample. Consistent evidence for reciprocal effects of schizophrenia on prefrontal and temporal-limbic regions indicates the importance of utilizing methods for network analysis of functional imaging data.…”
Section: Discussionsupporting
confidence: 89%
“…Given the role of the anterior cingulate in monitoring of error commission [Ghering et al, 1993], Carter et al [2001] speculated that increased activity in the anterior cingulate and decreased activity in the DLPFC might occur if patients have impaired attentional control leading to greater response conflict and demands for error monitoring. The increased frontal pole activity found in the current study has also been seen in previous studies of verbal episodic memory [Heckers et al, 1998;Ragland et al, 2001] and attributed to increased retrieval effort in the patient sample. Consistent evidence for reciprocal effects of schizophrenia on prefrontal and temporal-limbic regions indicates the importance of utilizing methods for network analysis of functional imaging data.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, schizophrenia patients showed less STG deactivation (relative overactivation) and a positive prefrontal-STG correlation. Further evidence of reciprocal changes in left frontal and left temporal regions was provided by Yurgelen-Todd et al (1996) in an fMRI study of word fluency; by Andreasen et al (1997) in a resting-state PET study; and by Ragland and colleagues in a series of studies of word encoding and recognition (Ragland et al, 2001;.…”
Section: Introductionmentioning
confidence: 90%
“…Converging lines of evidence, including postmortem (see for review in Harrison, 1999), in vivo MRI (see for review in Shenton et al, 2001), neuropsychological (Saykin et al, 1991), and functional imaging studies, point to abnormal medial temporal function in schizophrenia. Functional imaging studies have shown abnormalities of these regions during a resting state, (Nordahl et al, 1996;Heckers et al, 1998;Medoff et al, 2001;Tamminga et al, 1992) and abnormal modulation during such tasks as novel picture encoding (Zorrilla et al, 2002), episodic memory encoding (Ragland et al, 2001;Jessen et al, 2003) and retrieval (Heckers et al, 1998;Ragland et al, 2001;Jessen et al, 2003;Weiss et al, 2003).…”
Section: Hippocampal/parahippocampal Regions: Normal Function and Abnmentioning
confidence: 99%